FRACTIONATION OF CARBOHYDRATES AND PROTEINS IN TIFTON 85 BERMUDAGRASS HAY AT DIFFERENT CUTTING LEVELS AND STORAGE TIME - Monteiro Sunahara, Samantha Mariana; Neres, Marcela Abbado; Wobeto Sarto, Jaqueline Rocha [UNESP]; Nath, Caroline Daiane; Scheidt, Kacia Carine; Zambom, Maximiliane Alavarse (Univ Federal Uberlandia, 2018)
This study aimed to evaluate the fractionation of carbohydrates and protein of grass hay Tifton 85 bermudagrass under two cutting heights in relation to ground level (0.04 and 0.08 m) during 120 days of storage. Samples were collected in the baling and hay stored in shed at 30, 60, 90 and 120 days of storage, after, it was subjected to laboratory procedures, in which the levels of soluble carbohydrates were determined, carbohydrate fractionation and protein fractionation. The results were studied in a randomized complete block design with split plot with two treatments allocated the plots: cutting height of 0.04 to 0.08 m from the ground and five times in the subplots: baling, 30, 60, 90 and 120 days of storage hay, with five repetitions. The soluble carbohydrate concentration hay responded in a quadratic manner to the storage time for cutting heights of 0.04 and 0.08 m above soil level; minimum values of 11.53 and 10.70 g kg -1 of DM were estimated for 93.44 and 91.16 storage days, respectively. The carbohydrate fraction A + B1 responded negatively linear to periods of storage evaluated in both cutting heights. The contents of the carbohydrate fraction B2 and proteins A and C exhibited a positive linear response to storage time for a cutting height of 0.04 m and a quadratic effect for hay cutting height at 0.08 m above soil level, with an opposite behavior for both cutting heights for the B1 protein levels and C carbohydrate fraction. The B2 fraction showed a negative linear response as a function of storage time, with a reduction in the fraction of 0.09 and 0.11 percentage units for each day of storage, for hay cutting height of 0.04 and 0.08 m, respectively. The B3 fraction responded quadratically to the storage time, the two studied cutting heights. The storage of Tifton 85 hay cut at 0.04 m above soil level for 120 days leads to a decrease in fractions of rapid ruminal degradation and increase of the indigestible fraction in carbohydrate and protein fractions. Based on the results obtained it is recommended the cutting of the Tifton 85 bermuda grass forage to produce hay at 0.08 m and its storage up to 30 days provided that under ideal conditions.
Keywords: Forage conservation; Haymaking; Nitrogen compounds; Starch